Evaluation of five CAD/CAM materials by microstructural characterization and mechanical tests: a comparative in vitro study - Nesrin Sonmez; Pinar Gultekin; Volkan Turp; Gokhan Akgungor; Deniz Sen; Eitan Mijiritsky (BMC, 2018)
Abstract Background Polymer infiltrated ceramics and nano-ceramic resins are the new restorative materials which have been developed in order to enhance the adverse properties of glass-matrix ceramics and resin composites. The aim of the present in vitro study was to evaluate the characteristics of various CAD/CAM materials through mechanical, microstructural, and SEM analysis. Methods Five test groups (n = 22) were formed by using the indicated CAD/CAM blocks: VITA Enamic (VITA Zahnfabrik), Lava Ultimate (3 M ESPE), IPS e.max CAD (Ivoclar Vivadent), IPS Empress CAD (Ivoclar Vivadent), and VITA Mark II (VITA Zahnfabrik). Two specimens from each test group were used for XRD and EDS analysis. Remaining samples were divided into two subgroups (n = 10). One subgroup specimens were thermocycled (5 °C to 55 °C, 30s, 10,000 cycles) whereas the other were not. All of the specimens were evaluated in terms of flexural strength, Vickers hardness, and fracture toughness. Results were statistically analyzed using two-way ANOVA, one-way ANOVA, Tukey's HSD, and Student's t tests (α = .05). Fractured specimens were evaluated using SEM. Results The highest Vickers microhardness value was found for VITA Mark II (p < .001), however flexural strength and fracture toughness results were lowest conversely (p < .05). IPS e.max CAD was found to have the highest flexural strength (p < .001). Fracture toughness of IPS e.max CAD was also higher than other tested block materials (p < .001). Lava Ultimate and VITA Enamic's mechanical properties were affected negatively from thermocycling (p < .05). Microhardness, flexural strength, and fracture toughness values of Lava Ultimate and VITA Enamic were found to be similar to VITA Mark II and IPS Empress CAD groups. Conclusions It should be realised that simulated aging process seem to affect ceramic-polymer composite materials more significantly than glass ceramics.